Запорізький край в адміністративно-територіальних реформах більшовицької влади 1920-1930-х рр. (Zaporizhzhia Historical Review, 2021)
The article gives a historical retrospection of administrative and territorial changes in Zaporizhzhya region made by Bolshevik authorities in 20-30ies of the XXth century. The process of creating Zaporiz’ka region is described. The attention is paid to the fact that administrative and territorial changes hadn’t taken into account neither historical traditions nor national specificity and therefore resulted in deregulation of public administration and caused tragic consequences for the population.